2021
DOI: 10.3390/ijms22041802
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cytotoxicity of Complexes with N,N,N-Donor Dipodal Ligand in Tumor Cells

Abstract: The present article demonstrates selective cytotoxicity against cancer cells of the complexes [Co(LD)2]I2∙CH3OH (1), [CoLD(NCS)2] (2) and [VOLD(NCS)2]∙C6H5CH3 (3) containing the dipodal tridentate ligand LD = N,N-bis(3,5-dimethylpyrazol-1-ylmethyl)amine), formed in situ. All tested complexes expressed greater anticancer activities and were less toxic towards noncancerous cells than cisplatin. Cobalt complexes (1 and 2) combined high cytotoxicity with selectivity towards cancer cells and caused massive tumour c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…In conclusion, the above results of morphology observation and cell viability assays demonstrated that β-Co(OH) 2 NSs have certain selectivity to normal cells and cancer cells, and have significantly stronger cytotoxicity to cancer cells. The selective cytotoxicity of β-Co(OH) 2 NSs to cancer cells is similar to that of cobalt( ii ) complexes 35,36 or cobalt-based nanomaterials 37,38 reported previously in the literature. This suggests that this tumor cell-selective toxicity may be attributed to the presence of cobalt.…”
Section: Resultssupporting
confidence: 85%
“…In conclusion, the above results of morphology observation and cell viability assays demonstrated that β-Co(OH) 2 NSs have certain selectivity to normal cells and cancer cells, and have significantly stronger cytotoxicity to cancer cells. The selective cytotoxicity of β-Co(OH) 2 NSs to cancer cells is similar to that of cobalt( ii ) complexes 35,36 or cobalt-based nanomaterials 37,38 reported previously in the literature. This suggests that this tumor cell-selective toxicity may be attributed to the presence of cobalt.…”
Section: Resultssupporting
confidence: 85%
“…MTT formazan generated during incubation was dissolved and the absorbance was recorded at 550 nm (the reference wavelength was 690 nm) using a microplate reader Infinite M200 Pro, Tecan, Austria. IC 50 values were calculated from the concentration—response curves (IC 50 was the concentration [μM/L] of a tested compound required to decrease the cell proliferation to 50% of the control) [ 32 ]. All data were expressed as arithmetic mean values with standard deviation (M; ±SD).…”
Section: Methodsmentioning
confidence: 99%
“…Toxicity effect of the complexes was evaluated on normal human cell lines comprises of (WISH-ATCC-CCL-25, human epithelial amnion (liver cell lines), and MRC-5-ATCC-CCL-171, human lung fibroblast cell lines), using MTT method. 36,37 Samples concentrations of 50 and 100 μM were used against these cell lines. 200 μL representing ((1 × 10 4 cells per well) was seeded into 96-well plates and incubated at 37 °C for 24 hours in 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%